Jawabanmu

Jawaban paling cerdas!
2014-05-28T12:57:55+07:00
 f(x) = ax² + bx + c ⇒ f(1) ⇒  a + b + c = 0
                             ⇒ f(3) ⇒9a + 3b + c = 0 -
                                            - 8a - 2b = 0 ⇒ 2b = - 8a ⇒ b = -4a
D/-4a = 1 ⇒ b² - 4ac = 1
                ⇒ (-4a)² - 4ac = 1
                ⇒ 16a² -4ac = 1
                ⇒ 4a(4a - c) = 1
4a = 1      dan 4a - c = 1
  a =1/4            1 - c = 1
                             c = 0
b = -4a
b = -4(1/4) = -1
Jadi f(x) = 1/4 x² -x

3 3 3